Sparse and continuous sampling approaches to fMRI of overt vocalization tasks - Dawn L. Merrett; Chris Tailby; David F. Abbott; Graeme D. Jackson; Sarah J. Wilson (NeuroImage: Reports)
Sparse temporal sampling has become the dominant paradigm for functional magnetic resonance imaging studies of auditory stimuli or verbal responses, as it allows the presentation or production of stimuli during the relatively quiet periods when there is no gradient switching and ensures that task-related movements are not occurring during scan acquisitions. To date, however, there has been no direct comparison between sparse and continuous acquisition protocols for overt auditory-verbal studies (i.e., speaking or singing). The aim of this study was to determine whether sparse temporal sampling would reduce movement artefacts and show better network activation for overt singing compared to continuous imaging. Fifteen healthy adults performed the same overt singing task under both sparse and continuous scanning conditions. We noted significant variations in signal intensity between adjacent slices in our sparse acquisition, with (odd-numbered) slices acquired in the second half of each volume acquisition being of lower intensity and showing less reliable task-related activation, and thus requiring the removal of these slices prior to preprocessing. Edge artefacts, presumably due to movement, were observed in both acquisition types at a subthreshold level, although ventricular space artefacts were more apparent in the continuous data. However, statistical comparison revealed no significant differences in functional activation nor in motion correction parameters. Our results show that sparse imaging has the potential to introduce significant image artefacts affecting downstream analyses. While sparse sampling provides benefits that may be essential for certain studies (e.g., periods free from scanner noise), the technical requirements of such sequences should not be overlooked and inspection of raw data is essential. Our data also show that continuous imaging can be used for overt response auditory-verbal studies and may be of wider utility than previously appreciated.